Calculating regional tissue volume for hyperthermic isolated limb perfusion: Four methods compared. Issue 12 (December 2016) - Cecchin, D.; Negri, A.; Frigo, A.C.; Bui, F.; Zucchetta, P.; Bodanza, V.; Gregianin, M.; Campana, L.G.; Rossi, C.R.; Rastrelli, M.
Abstract: Introduction: Hyperthermic isolated limb perfusion (HILP) can be performed as an alternative to amputation for soft tissue sarcomas and melanomas of the extremities. Melphalan and tumor necrosis factor-alpha are used at a dosage that depends on the volume of the limb. Regional tissue volume is traditionally measured for the purposes of HILP using water displacement volumetry (WDV). Although this technique is considered the gold standard, it is time-consuming and complicated to implement, especially in obese and elderly patients. Aim: The aim of the present study was to compare the different methods described in the literature for calculating regional tissue volume in the HILP setting, and to validate an open source software. Methods: We reviewed the charts of 22 patients (11 males and 11 females) who had non-disseminated melanoma with in-transit metastases or sarcoma of the lower limb. We calculated the volume of the limb using four different methods: WDV, tape measurements and segmentation of computed tomography images using Osirix and Oncentra Masterplan softwares. Results and conclusion: The overall comparison provided a concordance correlation coefficient (CCC) of 0.92 for the calculations of whole limb volume. In particular, when Osirix was compared with Oncentra (validated for volume measures and used in radiotherapy), the concordance was near-perfect for the calculation of the whole limb volume (CCC = 0.99). With methods based on CT the user can choose a reliable plane for segmentation purposes. CT-based methods also provides the opportunity to separate the whole limb volume into defined tissue volumes (cortical bone, fat and water).